2020
DOI: 10.1155/2020/8831735
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Peptide Improves Neurite Outgrowth from Spiral Ganglion Neurons In Vitro through a cGMP-Dependent Manner

Abstract: The spiral ganglion neurons (SGNs) are the primary afferent neurons in the spiral ganglion (SG), while their degeneration or loss would cause sensorineural hearing loss. As a cardiac-derived hormone, atrial natriuretic peptide (ANP) plays a critical role in cardiovascular homeostasis through binding to its functional receptors (NPR-A and NPR-C). ANP and its receptors are widely expressed in the mammalian nervous system where they could be implicated in the regulation of multiple neural functions. Although prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…As shown in Figure 2 , ANP ( Figure 2A ) and its receptors’ ( Figures 2B,C ) immunoreactivities were observed in the SG regions along the length of the cochlear tonotopic axis without any noticeable apical-to-basal gradients. The representative images of cryosectioned tissues from the mid-cochlear turn revealed that the immunoreactivities of ANP ( Figure 2A 2 ), NPR-A ( Figure 2B 2 ), or NPR-C ( Figure 2C 2 ) were colocalized with TUJ1-positive neuronal somata of SGNs, which was consistent with our previous results ( Sun et al, 2013 , 2014 , 2020 ). The similar distribution patterns of ANP ( Figure 2A 2’ ), NPR-A ( Figure 2B 2’ ), and NPR-C ( Figure 2C 2’ ) were observed in the cochlear SGNs, and they were predominantly immunoreactive in the neuronal perikarya, including the cytoplasm and plasma membrane of SGNs.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…As shown in Figure 2 , ANP ( Figure 2A ) and its receptors’ ( Figures 2B,C ) immunoreactivities were observed in the SG regions along the length of the cochlear tonotopic axis without any noticeable apical-to-basal gradients. The representative images of cryosectioned tissues from the mid-cochlear turn revealed that the immunoreactivities of ANP ( Figure 2A 2 ), NPR-A ( Figure 2B 2 ), or NPR-C ( Figure 2C 2 ) were colocalized with TUJ1-positive neuronal somata of SGNs, which was consistent with our previous results ( Sun et al, 2013 , 2014 , 2020 ). The similar distribution patterns of ANP ( Figure 2A 2’ ), NPR-A ( Figure 2B 2’ ), and NPR-C ( Figure 2C 2’ ) were observed in the cochlear SGNs, and they were predominantly immunoreactive in the neuronal perikarya, including the cytoplasm and plasma membrane of SGNs.…”
Section: Resultssupporting
confidence: 90%
“…Sci. Rep. 6:29621. doi: 10.1038/srep29621 He, Z.-H., Zou, S.-Y., Li, M., Liao, F.-L., Wu, X., Sun, H.-Y., et al (2020). The nuclear transcription factor FoxG1 affects the sensitivity of mimetic aging hair cells to inflammation by regulating autophagy pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These pathways were directly related to neurite development. Also, the enriched items included some pathways which have been demonstrated closely related to neurite development, such as the PI3K-AKT signaling pathway (Zhao et al, 2020), mTOR signaling pathway (Wen et al, 2020), cGMP-PKG signaling pathway (Sun et al, 2020), thyroid hormone signaling pathway (Poddar et al, 1996), and calcium signaling pathway (Zhao et al, 2019; Figure 2E).…”
Section: Rf-emf Exposure Induced Transcriptomic Changes Related To Neurite Outgrowthmentioning
confidence: 99%